Total mercury and methylmercury levels in Brazilian Amazon fish: A scope review with meta-analysis and local population health risk assessment - Milena Dutra Pierezan; Rodrigo Barcellos Hoff; Eliane Teixeira Marsico; Silvani Verruck (Journal of Trace Elements and Minerals)
Introduction: The Brazilian Amazon has one of the richest biomes and the largest source of freshwater on the planet. However, anthropogenic activities have also turned this region into one of the highest points of human exposure to mercury ever recorded. Therefore, the aim of the present work was to perform a scope review with meta-analysis in order to evaluate the total mercury (THg) and methylmercury (MeHg) levels in Brazilian Amazon fish, as well as to carry out a local population health risk assessment. Methods: A literature search was systematically performed in research databases and gray literature, remaining 14 studies from 2017 to 2022 for final analysis. The studies were submitted to raw mean and subgroup meta-analysis, followed by a risk characterization and the calculation of a maximum safe consumption of fish for the Amazonian population. Results: The selected studies covered 4 Amazonian states, as well as included the analysis of >30 fish species of different trophic levels and sampling in >15 cities. The overall total mercury mean obtained for Brazilian Amazon fish was 0.29 ug g⁻¹. Significant difference was observed between THg levels according to fish trophic level (p < 0.05), which reinforces the MeHg biomagnification. When THg levels from all fish samples were pooled, it was not observed a significant difference among the Amazonian states and the fish sampling season. However, significant variations between microregions and species-specific variations over the seasons should not be discarded. All estimated daily methylmercury intake exceeded the reference dose of 0.1 ug kg BW⁻¹ day⁻¹, resulting in a hazard quotient (HQ) greater than 1 and indicating a risk of chronic exposure by the local population. The maximum safe consumption of fish calculated based on the overall total mercury mean was set as 31, 147 and 173 g week⁻¹ for children, adult women and adult men, respectively, which is much lower than the reality of consumption by the riverside communities (2870 g week⁻¹). Conclusion: There is an urgent need to reduce Hg exposure levels in the region as well as to recommend other protective nutritional strategies to the local population such as defining the fish species with lower mercury contamination levels and their safe weekly consumption.